2020
DOI: 10.1108/aeat-05-2020-0087
|View full text |Cite
|
Sign up to set email alerts
|

Exergy analysis of a three-spool turboprop engine during the flight of a cargo aircraft

Abstract: Purpose This study aims to introduce exergy analysis of a three-spool turboprop engine during the complete flight. Design/methodology/approach In this study, a flight scenario of the aircraft is assumed. Operating parameters of the aircraft and its engine are modelled based on the assumed flight scenario with the aid of a genuine code. And then performance analysis of the engine is performed for each flight path point with the aid of exergy. Findings At the end of the study, major exergy parameters of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…To comprehend the mechanism regarding the conversion of energy forms to each other necessitates the first law of thermodynamics, whereas whose second law determines how much quality energy forms convert to each other. When implementing both laws of thermodynamics known as exergy analysis, possible improvements about the system or components could be detected, enabling the engineers to increase system efficiency in designing process (Dinc et al 2020 ). Since exergetic method considers both quantity and quality of energy, the important knowledge such as exergy destruction and improvement potential rate for thermal systems could be obtained (Balli and Caliskan 2021 ).…”
Section: Methodology and Thermodynamics Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…To comprehend the mechanism regarding the conversion of energy forms to each other necessitates the first law of thermodynamics, whereas whose second law determines how much quality energy forms convert to each other. When implementing both laws of thermodynamics known as exergy analysis, possible improvements about the system or components could be detected, enabling the engineers to increase system efficiency in designing process (Dinc et al 2020 ). Since exergetic method considers both quantity and quality of energy, the important knowledge such as exergy destruction and improvement potential rate for thermal systems could be obtained (Balli and Caliskan 2021 ).…”
Section: Methodology and Thermodynamics Backgroundmentioning
confidence: 99%
“…In terms of thermodynamics, to alleviate fuel consumption, thereby environmental damage requires removing irreversibility from the system as much as possible (Dinc et al 2020 ). In this context, energy, emission, exergy and economy issues are related with each other employing thermodynamics laws to thermal systems.…”
Section: Introductionmentioning
confidence: 99%
“…In general, performance evaluations, as systems that operate depending on power generation, for different altitude conditions, it depends on different fuel consumption and examples of this can be seen in the literature. For example Dinc et al (2020) investigated performance analysis of the cargo aircraft three-spool engine is performed for each flight path point with the aid of exergy and calculated major exergy parameters of the engine during the complete flight. For this, especially in flight planning, engine fuel consumption estimates are made and managed based on these predictions.…”
Section: Environmental Effects In Flight Processmentioning
confidence: 99%
“…Dinç et al have conducted the exergy analysis of a threespool turboprop engine during the complete flight. They found that the main reason for the improvement in exergy efficiency was directly related to the decrease in ambient temperature and pressure due to altitude change (Dinc et al, 2020).…”
Section: Introductionmentioning
confidence: 99%